Protozoários de vida livre em ambientes aquáticos do RN: ocorrência, caracterização e importância para a educação básica - Medeiros, Maria Luisa Quinino de (2012)
Water is considered an essential right to life, besides being a determinant of economic development and social welfare, represented by both the quantity available, and the quality. In semi-arid Northeast, droughts occurring on a regular basis combined with human activities, aggravate the situation regarding the conservation of water resources in this area. To alleviate this condition is common to construction of artificial reservoirs, such as reservoirs and dams. As in natural aquatic environments, these reservoirs are potential sites for the proliferation, growth and development of diverse biological communities, whether of animals, plants and microorganisms. Research on the composition and ecology of these communities, especially microbial, are still restricted. One of the least studied groups in these environments are free-living protozoa, which over time have been neglected and after discoveries about its various functions in the aquatic ecosystem are beginning to receive more attention from scholars. They are, in quantitative terms, the most important consumers of microorganisms (mainly bacteria and algae) in aquatic environments, and therefore control the abundance of these. They may therefore influence the structure of the aquatic food chain in terms of species composition, abundance, biomass and biodiversity. Despite the recognition of the importance of protozoa in the final of the trophic transfer in aquatic environments, there are few data and, in general, are still precarious knowledge of them. Given the importance of protozoa in aquatic environments and the paucity of research on this group, especially in the state of Rio Grande do Norte, the present study aimed at identifying the genus and species of free-living protozoa that are present in the Armando Ribeiro Gonçalves Dam as well as to relate the occurrence and dynamics of the trophic conditions in the environment in which they are inserted, in order to support the hypothesis that species that are in these environments can serve to indicate the water quality. We observed the presence of 65 taxa of free-living protozoa, of which 29 were identified at the species level. There was a similarity space in taxonomic composition of protozoa, suggesting a possible regulation of this type of community for limnological variables other than those studied in this work (chlorophyll a, pH, temperature). Although it was aimed to analyze the conceptions of teachers and students from nearby towns Dam Armando Ribeiro Gonçalves, on issues relating to water quality and the role of protozoa. For this, we applied questionnaires with teachers and pupils of public schools of San Rafael and Itajá. It was concluded that teachers and students recognize the multi-dam Armando Ribeiro Gonçalves, although unaware of important aspects of the dynamics and ecology of this environment. Conceptions of teachers and students are matched at various times, especially with regard to waterborne diseases. In an attempt to identify possible misconceptions about the knowledge of the protozoa, assuming that these organisms have neglected their ecological role, and are seen as only, disease, a study was done with teachers and students, following a particular methodology that allowed look so clear and precise results. It was clear that knowledge about the free-living protozoa is still quite limited. The alternative conceptions that were found show a direct relation of protozoans and diseases. From the data obtained by these studies, we planned a series of science communication activities, environmental education and health education in schools close to study environments in order to promote a didactic transposition of accumulated knowledge about these organisms, favoring continuing education of teachers and the increase of information to the local community through the knowledge of biodiversity and ecology of these organisms. Moreover, the results found in this study and reflections on it that led to propose the elaboration of a book Readers with an emphasis on the group of freeliving protozoa in the populations for use in public schools in the region where it was developed the semiarid work